Self-Compassion and Dispositional Mindfulness Are Associated with Parenting Styles and Parenting Stress: the Mediating Role of Mindful Parenting - Gouveia, M. J. (2016)
Mindful parenting is a recent concept in parenting studies and has been described as a set of parental practices or skills that seek to enhance moment-to-moment awareness in the parent–child relationship. Some studies suggest that mind- ful parenting is associated with parent’s dispositional mindful- ness and self-compassion, while others suggest that mindful parenting can reduce parenting stress and promote a positive parenting. However, there is no study describing an integra- tive model with these variables. The present study explored whether parents’ dispositional mindfulness and self- compassion are associated with parenting stress and parenting styles through mindful parenting. A sample of 333 parents (87 fathers, 246 mothers) between the ages of 27 and 63 years participated in the study. The results revealed that higher levels of dispositional mindfulness and self-compassion are associated with higher levels of mindful parenting that, in turn, is associated with lower levels of parenting stress, higher levels of authoritative parenting style, and lower levels of authoritarian and permissive parenting styles. This study pro- vides relevant and innovative data on mindful parenting re- search by clarifying some of the modifiable variables that may facilitate the adoption of mindful parenting and of adaptive parenting styles and decrease parenting stress. These findings have important clinical implications for the identification of groups of more vulnerable parents who would benefit most from mindful parenting interventions.